Effect of physical activity on anxiety levels in pregnant women - Inga Janik; Anna Fabian-Danielewska; Katarzyna Korabiusz; Mirela Niedzielska; Agata Wawryków (Kazimierz Wielki University, 2017)
Pregnancy is a very important period in a woman's life, but it is often associated not only with positive emotions, but also with negative emotions such as anxiety, stress or depression. Women most often fear birth and various medical complications during pregnancy. Very often their unpleasant experiences at the beginning such as nausea, fatigue and strong anxiety cause them to give up their physical activity. Numerous studies show that the physical activity of pregnant women has a positive impact on mother and child health. First and foremost, it is a powerful preventive agent in cardiovascular disease, diabetes mellitus, but also has a beneficial effect on the well-being of future mothers, including lowering anxiety and lowering the incidence of postpartum depression. That is why it is so important to educate pregnant women what exercises are most beneficial for them.